Method for evaluating sintering activity of silver powder

By measuring the change in volume before and after sintering of silver powder, calculating the volume shrinkage rate, and directly evaluating the sintering activity of silver powder, solving the problems of cumbersome evaluation steps and unquantifiable results in the prior art, and achieving efficient, objective and quantifiable evaluation of silver powder sintering activity.

CN119643369APending Publication Date: 2025-03-18DONGFANG ELECTRIC CHENGDU INTELLIGENT TECH CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411562739.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art lacks a method for directly testing sintering activity for silver powder, resulting in cumbersome evaluation steps, long cycles, and subjective and unquantifiable evaluation results.

Method used

By measuring the change in volume before and after sintering of silver powder, and calculating the volume shrinkage rate, the sintering activity of silver powder is evaluated. This method directly tests silver powder, eliminating the process of silver paste preparation and sintering of terminal devices.

Benefits of technology

It realizes efficient, objective and quantifiable evaluation of silver powder sintering activity, and can quickly predict the sintering density of silver electrodes in terminal devices and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643369A_ABST
    Figure CN119643369A_ABST
Patent Text Reader

Abstract

The invention discloses an evaluation method for silver powder sintering activity, and belongs to the technical field of silver powder performance testing, the method comprises the following steps: putting silver powder into a mold for sintering, taking out a silver material after sintering, immersing the silver material into an oily solution, discharging bubbles, taking out the immersed silver material, and removing the oily solution on the surface of the silver material to obtain a sintered silver sample; the volume shrinkage rate of the sintered silver sample is calculated by utilizing the volumes of the silver powder and the silver sample before and after sintering, and the sintering activity of the silver powder is evaluated by utilizing the volume shrinkage rate. According to the method, the sintering activity of the silver powder is evaluated by measuring the volume shrinkage rate after sintering according to the volume change of the silver powder before and after sintering, the volume shrinkage rate is large, and the sintering activity is high; the method has the advantages of small volume shrinkage, low sintering activity, high efficiency, objectivity and quantifiability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silver powder performance testing, and in particular, is a method for evaluating the sintering activity of silver powder. Background Art

[0002] Silver has high conductivity and is not easily oxidized. Silver powder is widely used in the fields of photovoltaics and electronics as a conductive filler for conductive pastes. During the application process, silver powder is mixed with other materials such as organic materials, first made into a conductive paste such as silver paste, or a conductive glue such as silver glue, and then printed on terminal devices such as photovoltaic cells or varistors by printing methods such as screen printing or spraying to make electrodes. Depending on the application, the printed silver electrode will be sintered at different temperatures to obtain the final silver electrode. The sintering activity of silver powder directly determines the density of the silver electrode itself, thereby affecting the conductivity of the silver electrode itself and the contact conductivity between the silver electrode and the terminal device such as a photovoltaic cell or a varistor, and ultimately affects the electrical properties of the terminal device, such as the efficiency of the photovoltaic cell or the flow rate of the varistor. Therefore, a test method for the sintering activity of silver powder is developed to evaluate the sintering activity of silver powder, which can not only analyze the influence of silver powder on the electrical properties of the terminal device, but also select silver powder in a targeted manner to adapt to different terminal devices.

[0003] At present, there is no sintering activity test method developed specifically for silver powder. There is only a method for evaluating the sintering activity of terminal devices such as silver electrodes of photovoltaic cells after silver powder is made into paste and printed. For example, Zhang Yaping et al. mentioned in "The influence of glass powder on the performance of silicon solar cells" (Journal of the Chinese Ceramic Society, Vol. 36, No. 7, July 2008, 1022-1025) that the influence of glass powder on the sintering degree of silver powder can be judged by SEM photos of silver electrodes of solar cells, thereby judging the density of silver electrodes; Chen Yinglong et al. also mentioned in "The influence of positive silver paste silver powder characteristics and sintering process on solar cell performance" (Powder Metallurgy Industry, Vol. 22, No. 6, December 2012, 17-24) that silver powders with different particle sizes, agglomeration factors, tap density, and morphology can be made into silver The slurry was screen-printed, dried, and sintered at 870°C to obtain the front silver electrode, and the SEM image of the sintered silver electrode was used to judge the influence of different silver powders on the morphology of the sintered silver electrode, thereby affecting the resistivity and adhesion of the electrode; and Sun Jiaruo et al. mentioned in "Characterization of Highly Crystalline Monodisperse Silver Powder and Analysis of Low-Temperature Sintering Activity" ("Gold", Issue 04, 2023, 5-8) that four silver powders of different particle sizes were made into slurry, electrodes were printed on HJT batteries, and sintered at 200°C. The SEM image of the electrode after sintering was used to judge the melting state of the silver powder and the network path formed.

[0004] It can be seen that the existing evaluation methods for the sintering activity of silver powder are to make silver powder into slurry, then print and sinter it, and then evaluate the sintering activity of the silver electrode of the terminal device. This method has cumbersome steps and a long evaluation cycle. The evaluation is to judge the sintering activity of silver powder through SEM images, but SEM can only take pictures of local microscopic states, which has certain limitations, and the judgment is too subjective and cannot be objectively evaluated. Its sintering activity evaluation cannot be quantified. Summary of the invention

[0005] The present invention aims to provide a method for evaluating the sintering activity of silver powder. The evaluation method is a sintering activity evaluation process directly performed on silver powder. The volume change of the silver powder before and after sintering is utilized, and the sintering activity of the silver powder is evaluated by measuring the volume shrinkage rate after sintering. The larger the volume shrinkage, the higher the sintering activity; the smaller the volume shrinkage, the lower the sintering activity. The method has the advantages of being efficient, objective and quantifiable.

[0006] The present invention is achieved through the following technical scheme: a method for evaluating the sintering activity of silver powder, wherein the silver powder is loaded into a mold for sintering, the silver material is taken out after sintering and immersed in an oily solution, bubbles are discharged, the immersed silver material is taken out and the oily solution on its surface is removed to obtain a sintered silver sample, the volume shrinkage rate of the sintered silver sample is calculated by using the volumes of the silver powder and the silver sample before and after sintering, and the volume shrinkage rate is used to evaluate the sintering activity of the silver powder.

[0007] The silver powder is filled into a mold, and after vibration or compaction, the volume in the mold is taken as the volume of the silver powder before sintering.

[0008] The sintering is carried out in a muffle furnace, the sintering temperature is controlled to be 30-900° C., and the sintering time is 1-60 minutes.

[0009] The sintering temperature is 200-500°C.

[0010] The oily solution comprises one or more of organic acid, organic amine, azole compound and Span.

[0011] The time for the silver material to be immersed in the oily solution is controlled to be 15 to 180 minutes.

[0012] The sintered silver sample is weighed to obtain the mass of the silver sample, which is recorded as m1. The silver sample is then placed in water, and the temperature at this time is recorded as t. The mass of the silver sample after deducting the buoyancy is weighed as m2. The volume of the sintered silver sample is calculated according to formula (1): V2=(m1-m2) / ρ (1) Among them, V2 is the volume of the silver sample after sintering, and ρ is the density of water corresponding to the water temperature t.

[0013] The volume shrinkage of the silver sample after sintering was calculated according to formula (2): η=(V2-V1) / V1×100% (2) Wherein, η is the volume shrinkage, V1 is the volume of the silver powder before sintering, and V2 is the volume of the silver sample after sintering.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention innovatively proposes a method for directly evaluating the sintering activity of silver powder, eliminating the need for subsequent silver paste preparation, printing, sintering and other processes. The evaluation results of the sintering activity of silver powder are used to predict the sintering density of the silver electrode in the terminal device, thereby improving efficiency and reducing costs.

[0015] (2) When evaluating the sintering activity of silver powder, the method of the present invention uses the Archimedes principle to evaluate the sintering activity of silver powder by measuring the volume shrinkage rate after sintering through the change of drainage volume before and after sintering. The larger the volume shrinkage, the higher the sintering activity; the smaller the volume shrinkage, the lower the sintering activity. Compared with the existing method of judging by SEM images of silver electrodes of terminal devices, this method has the advantages of being more objective and quantifiable data.

[0016] (3) The present invention can make the silver powder loaded in the mold more compacted by adding a vibration or compaction process to the mold filled with silver powder before sintering, thereby promoting the sintering of the silver powder. When compacting, the magnitude of the force should be controlled so as not to destroy the morphology and particle size of the silver powder, thereby evaluating silver powders with similar sintering activity.

[0017] (4) The present invention can be better used for evaluating the sintering activity of silver powder by reasonably controlling the sintering temperature and sintering time during the sintering process. Too low a sintering temperature and too short a sintering time cannot evaluate the difference between silver powders with similar sintering activities.

[0018] (5) After sintering, the present invention immerses the silver material in an oily solution for a certain period of time to remove bubbles, thereby ensuring the stability of the reading during weighing on a balance in the subsequent step and improving the accuracy of the sintering activity evaluation. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image of the silver electrode made from the silver powder described in Example 1.

[0020] Figure 2 This is the SEM image of the silver electrode made from the silver powder described in Example 2.

[0021] Figure 3 This is the SEM image of the silver electrode made from the silver powder described in Example 3. DETAILED DESCRIPTION

[0022] The invention objectives, technical solutions and beneficial effects of the present invention are further described in detail below.

[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the claimed invention, and unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs.

[0024] The present invention proposes for the first time an efficient, objective and quantifiable sintering activity evaluation method directly for silver powder. Specifically, the Archimedean principle is adopted to measure the volume shrinkage rate after sintering by the change in the drainage volume before and after the sintering of the silver powder, and the volume shrinkage rate is used to evaluate the sintering activity of the silver powder. The larger the volume shrinkage rate, the higher the sintering activity of the silver powder; the smaller the volume shrinkage rate, the lower the sintering activity of the silver powder.

[0025] The steps can be summarized as follows: Step 1: Place silver powder in a fixed stacked state into a mold with a volume of V1 and fill it up.

[0026] In order to distinguish silver powders with similar sintering activities, it is necessary to improve the resolution of volume shrinkage. In this step, a sample preparation process can be added, namely: first, the silver powder loaded in the mold is vibrated or compacted, the purpose is to promote the sintering of the silver powder, while maintaining the original morphology and particle size of the silver powder, and then the mold and the filled silver powder are placed in a muffle furnace for sintering, wherein the vibration includes but is not limited to placing the mold filled with silver powder on a vibration table and vibrating it at a certain frequency and time to make the silver powder accumulate more densely; and the compaction includes but is not limited to using a press to apply a certain force to the upper surface of the silver powder loaded in the mold for a certain time to make the silver powder accumulate more densely, and the magnitude of the force is preferably not to destroy the morphology and particle size of the silver powder.

[0027] Step 2: directly placing the filled silver powder mold into a muffle furnace without any other treatment, and sintering at a specific temperature and time.

[0028] The sintering temperature can be controlled at 30-900° C., preferably 200-500° C., and the sintering time can be controlled at 1-60 min, preferably 1-30 min.

[0029] Step 3, taking out the sintered silver material and demoulding; Step 4: Immerse the demoulded silver material in an oily solution for 15 to 180 minutes to remove bubbles.

[0030] The oily solution includes, but is not limited to, organic acids, organic amines, azole compounds, Span, etc. The soaking time may preferably be 15 to 30 minutes.

[0031] Step 5, taking out the soaked silver material and removing the oily solution on its surface to obtain the sintered silver sample.

[0032] Place the sintered silver sample on a balance and weigh the sample mass, recorded as m1.

[0033] Step 6, lift the sintered silver sample and immerse it in a container filled with water, record the temperature of the water at this time, recorded as t, and weigh the mass of the silver sample after deducting the buoyancy, recorded as m2; Step 7: Calculate the drainage volume using formula (1), which is the volume of the silver sample after sintering.

[0034] V2=(m1-m2) / ρ (1) Among them, V2 is the volume of the silver sample after sintering, and ρ is the density of water corresponding to the water temperature t.

[0035] Step 8: Calculate the volume shrinkage of the silver sample after sintering using formula (2).

[0036] η=(V2-V1) / V1×100% (2) Wherein, η is the volume shrinkage, V1 is the volume of the silver powder before sintering, and V2 is the volume of the silver sample after sintering.

[0037] Step nine, evaluating the sintering activity of the silver powder according to the volume shrinkage rate of the silver sample.

[0038] The technical solution for achieving the purpose of the present invention is further described below through several specific embodiments. It should be noted that the technical solution claimed for protection by the present invention includes but is not limited to the following embodiments.

[0039] Embodiment 1: The average particle size is 1.14 μm, the specific surface area is 0.527 m 2 After the mold is filled with silver powder of 100 g, it is not compacted or vibrated, but processed according to the above steps of the present invention, the sintering temperature is controlled to be 350° C., the sintering time is 5 min, the soaking time is 30 min, and the soaking solution is stearic acid to obtain a silver sample, and then its volume shrinkage is calculated to be 14.785%.

[0040] Embodiment 2: The average particle size is 1.07 μm, and the specific surface area is 0.563 m 2 / g of silver powder is filled into a mold of the same volume as in Example 1. After filling, it is not compacted or vibrated, but treated according to the above steps of the present invention. The operating conditions are the same as in Example 1 to obtain a silver sample, and then its volume shrinkage is calculated to be 17.407%.

[0041] Embodiment 3: The average particle size is 1.02 μm, and the specific surface area is 0.59 m 2 / g of silver powder is filled into a mold of the same volume as in Example 1. After filling, it is not compacted or vibrated, but treated according to the above steps of the present invention. The operating conditions are the same as in Example 1 to obtain a silver sample, and then its volume shrinkage is calculated to be 17.901%.

[0042] Embodiment 4: The average particle size is 0.89 μm, and the specific surface area is 0.621 m 2 / g of silver powder is filled into a mold of the same volume as in Example 1. After filling, it is not compacted or vibrated, but processed according to the above steps of the present invention. The operating conditions are the same as in Example 1 to obtain a silver sample, and then its volume shrinkage is calculated to be 20.057%.

[0043] Embodiment 5: The particle size distribution is consistent, with d10=1.09μm, d50=1.73μm, d90=3.25μm, d95=3.53μm, d100=4.67μm, the average particle size is 1.03μm, and the specific surface area is the same as 0.57m 2 / g, but two kinds of silver powders with primary particle sizes of 40nm and 25nm respectively are filled into a mold of the same volume as in Example 1, and after filling, the mold is vibrated. The mold is placed on a vibration table, and the vibration frequency is controlled to be 300rpm for 5min. The treatment is carried out according to the above steps of the present invention, and the operating conditions are the same as in Example 1 to obtain silver samples, and then the volume shrinkage rates are calculated to be 24.111% and 24.647%.

[0044] Embodiment 6: The particle size distribution is consistent, with d10=1.09μm, d50=1.73μm, d90=3.25μm, d95=3.53μm, d100=4.67μm, the average particle size is 1.03μm, and the specific surface area is the same as 0.57m 2 / g, but two kinds of silver powders with primary particle sizes of 40 and 25 nm respectively were filled into a mold of the same volume as in Example 1, compacted after filling, and sintered according to the above steps using a press with a pressure of about 5 MPa for 5 min. The volume shrinkage rates of the prepared samples were 27.313% and 29.552% respectively.

[0045] Comparative Example 1: The silver powders of Example 1 and Example 2 were respectively filled into molds of the same volume as that of Example 1. After filling, the molds were not compacted or vibrated. Then, sintered silver samples were prepared according to the method of Example 1. The only difference was that the sintering temperature was 150° C. during the sintering process. The obtained silver powders were not sintered and could not be evaluated.

[0046] Comparative Example 2: The silver powders of Example 1 and Example 2 were respectively filled into molds of the same volume as that of Example 1. After filling, the molds were not compacted or vibrated. Then, sintered silver samples were prepared according to the method of Example 1. The only difference was that the sintering time was 1 min during the sintering process. The other operating conditions were the same as those of Example 1. The silver samples were prepared, and then their volume shrinkage rates were calculated to be 7.794% and 7.879%, respectively, with no obvious difference.

[0047] Comparative Example 3: The silver powders of Example 5 and Example 6 were respectively filled into molds of the same volume as that of Example 1. After filling, the molds were not compacted or vibrated. Then, sintered silver samples were prepared according to the method of Example 1. The operating conditions were the same as those of Example 1. The silver samples were obtained, and then their volume shrinkage rates were calculated to be 26.677% and 26.747%, respectively, with no obvious difference.

[0048] The same silver powder as in Examples 1 to 3 was used to prepare three silver samples in the same manner as in the examples, and the volume shrinkage was calculated, as shown in Table 1 below.

[0049] Table 1 Volume shrinkage of silver samples from different batches Furthermore, the data of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 3 are recorded in the following Table 2.

[0050] Table 2 From Table 2 above, we can see that: In Examples 1 to 4, as the average particle size of the silver powder decreases, the specific surface area increases, and the sintering activity of the silver powder increases, the corresponding volume shrinkage increases when the conventional sintering test is performed according to the method developed by the present invention. Compared with Examples 1 and 2, the sintering temperature of Comparative Example 1 is too low, and the sintering time of Comparative Example 2 is too short, so the difference in sintering activity of silver powders with different average particle sizes and specific surface areas cannot be evaluated.

[0051] In Example 5 and Example 6, the silver powders with the same particle size, particle size distribution, and specific surface area are different only in primary particle size. The silver powders with large primary particle size have fewer grain boundaries and weak sintering activity, while the silver powders with small primary particle size have more grain boundaries and strong sintering activity. The method of the present invention can evaluate the change in volume shrinkage by either vibration or compaction, and is consistent with the actual sintering activity change law. Compared with Example 5 and Example 6, Comparative Example 3 uses conventional sintering instead of vibration or compaction and then sintering, and cannot evaluate the sintering activity difference of silver powders with different primary particle sizes.

[0052] At the same time, for silver powders with the same specific surface area but different primary particle sizes, since the specific surface areas are similar, the discrimination accuracy of their volume recovery rates is limited. The method of the present invention can distinguish them based on vibration or compaction, as shown in Examples 5 and 6.

[0053] In summary, the method of the present invention changes the process of making silver electrodes by pulping, printing and sintering silver powder in the prior art, and then judging the sintering activity of the silver powder by SEM images. The evaluation result of the sintering activity of the silver powder can be quickly obtained after the silver powder is sintered, that is, the sintering activity of the silver powder can be evaluated by the volume shrinkage rate of the silver powder after sintering, so that the accurate evaluation of the sintering activity of the silver powder can be realized. Figures 1 to 3 As shown, they are SEM images of silver electrodes made from the silver powders described in Examples 1 to 3 using the same method. It can be seen from the figures that with the increase of shrinkage rate, the sintering activity of the three silver powders increases successively, and the corresponding SEM images of the silver electrodes show that the porosity decreases successively, and the sintering becomes denser successively.

[0054] In addition, the method of the present invention has more efficient and objective advantages than the prior art. The efficiency is reflected in that it saves the complex process of preparing silver paste from silver powder (preparing silver paste by mixing with a three-roll mill according to the paste formula), including but not limited to printing processes such as screen printing (printing the silver paste on the surface of the battery or other terminal device to form an electrode), and sintering (the battery cell or other terminal device enters the sintering furnace and is sintered at a certain temperature to make the silver electrode and the battery cell or other terminal device conductive). The silver powder can be directly sintered for evaluation, and the evaluation cycle is short; the objectivity is reflected in that the porosity shown in the SEM image is not used to characterize the sintering activity, but it is characterized by quantifiable data, namely the volume shrinkage rate, which is more conducive to rapid and accurate evaluation of the sintering activity of the silver powder and realizes mass production.

[0055] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for evaluating the sintering activity of silver powder, characterized in that: Silver powder is placed in a mold for sintering. After sintering, the silver material is taken out and immersed in an oily solution. After the bubbles are discharged, the immersed silver material is taken out and the oily solution on its surface is removed to obtain a sintered silver sample. The volume shrinkage of the sintered silver sample is calculated using the volumes of the silver powder and the silver sample before and after sintering, and the volume shrinkage is used to evaluate the sintering activity of the silver powder.

2. The evaluation method according to claim 1, characterized in that: The silver powder is filled into a mold, and after vibration or compaction, the volume in the mold is taken as the volume of the silver powder before sintering.

3. The evaluation method according to claim 1, characterized in that: The sintering is carried out in a muffle furnace, the sintering temperature is controlled to be 30-900° C., and the sintering time is 1-60 minutes.

4. The evaluation method according to claim 1, characterized in that: The sintering temperature is 200-500°C.

5. The evaluation method according to claim 1, characterized in that: The oily solution comprises one or more of organic acid, organic amine, azole compound and Span.

6. The evaluation method according to claim 1, characterized in that: The time for the silver material to be immersed in the oily solution is controlled to be 15 to 180 minutes.

7. The evaluation method according to claim 1, characterized in that: The sintered silver sample is weighed to obtain the mass of the silver sample, which is recorded as m1. The silver sample is then placed in water, the temperature of the water is recorded as t, and the mass of the silver sample after deducting the buoyancy is weighed as m2. The volume of the sintered silver sample is calculated according to formula (1): V2=(m1-m2) / ρ (1) Among them, V2 is the volume of the silver sample after sintering, and ρ is the density of water corresponding to the water temperature t.

8. The evaluation method according to claim 1, characterized in that: The volume shrinkage of the silver sample after sintering was calculated according to formula (2): η=(V2-V1) / V1×100% (2) Wherein, η is the volume shrinkage, V1 is the volume of the silver powder before sintering, and V2 is the volume of the silver sample after sintering.

Citation Information

Patent Citations

  • Method for detecting density of porous material

    CN102721627A

  • Method of testing porosity

    CN103134743A

  • Method for calibrating drop hammer volume

    CN109269939A

  • Method for measuring and calculating high-temperature sintering performance of iron-containing minerals and mineral sintering equipment

    CN113777126A

  • Method and equipment for real-time measurement of volume variation in polymerizing reaction by floatage method

    CN1320814A